Zakat Charity and Wealth Distribution: An Agent Based Computational Model - Muhammad Jaffer Asif (International Journal of Zakat, 2022)
An Agent Based Model (ABM) of wealth distribution (Wilensky, 1998) that creates representative Pareto pattern of wealth distribution, is customized to introduce Zakat (a charity in Islamic Finance @2.5% of net wealth). The impact of this small charity on the part of the rich changed the Pareto distribution of wealth in the model into a normal distribution. The redistribution as a result of Zakat also increased the net wealth of the model as a whole, thereby stimulating economic growth. The results stresses the importance of non-conventional handling of the issue and highlights the role of small charities in improving economic wellbeing.